Analisis Pengelolaan Dana Masjid Dalam Meningkatkan Sosial Ekonomi Masyarakat Di Kelurahan Murni Kota Jambi - Eja Armaz Hardi; GWI Awal Habibah; Dhea Kurnia Saputri (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
Managing mosque funds is an important part of running it development activities, existing activities and covering all aspects socio-economic society. However, the main problem is deep management of the funds of the Mosque At-Taufiq and Mosque Al-Ittihad is management funds that are not yet effeccctive and efficient and socio-economic coditions that are not yet possible realized optimally for society. The purpose of this thesis: 1. To understand the management of funds at the Mosque At-Taufiq and Mosque At-Ittihad. 2. To find out the socio-economics of the At-Taufiq Mosque and Al-Ittihad Mosque in Murni Village, Jambi City. Researchers use descriptive qualitative methods, namely methods that will analyze and examine data from mosque. Researchers collect data in the form of data collection techniques in the form of observation, documentation and interviews. The research show: 1. The form of fund management the two Murni Village Mosques use management, namely planning, organizing, actuating and controlling, where in managing mosque funds there are several things that must be done attention, namely transparency, accountability, fund collection (reception system funds, fund storage system, fund reporting system, disbursement system and incoming funds) and distribution of funds. 2. Running socio-economics in the At-Taufiq Mosque and Al-Ittihad Mosque have functions int the same field Idarah, Imarah sector and Riayah Sector. It is hoped that the results of this research will be useful for increasing knowledge, insight and input for parties both mosque and the community so they can know how to manage funds the correct mosque by using functions and principles Management for managing mosque funds or managing mosque funds can be carry out the socio-economic funds is an activity that very good for society.